Pseudomonas aeruginosa lipopolysaccharide inhibits Candida albicans hyphae formation and alters gene expression during biofilm development. (12th October 2012) - Bandara, H.M.H.N.; K Cheung, B.P.; Watt, R.M.; Jin, L.J.; Samaranayake, L.P.
Summary Elucidation of bacterial and fungal interactions in multispecies biofilms will have major impacts on understanding the pathophysiology of infections. The objectives of this study were to (i) evaluate the effect of Pseudomonas aeruginosa lipopolysaccharide (LPS) on Candida albicans hyphal development and transcriptional regulation, (ii) investigate protein expression during biofilm formation, and (iii) propose likely molecular mechanisms for these interactions. The effect of LPS on C. albicans biofilms was assessed by XTT‐reduction and growth curve assays, light microscopy, scanning electron microscopy (SEM), and confocal laser scanning microscopy (CLSM). Changes in candidal hypha‐specific genes (HSGs) and transcription factor EFG1 expression were assessed by real‐time polymerase chain reaction and two‐dimensional gel electrophoresis, respectively. Proteome changes were examined by mass spectrometry. Both metabolic activities and growth rates of LPS‐treated C. albicans biofilms were significantly lower (P < 0.05). There were higher proportions of budding yeasts in test biofilms compared with the controls. SEM and CLSM further confirmed these data. Significantly upregulated HSGs (at 48 h) and EFG1 (up to 48 h) were noted in the test biofilms (P < 0.05) but cAMP levels remained unaffected. Proteomic analysis showed suppression of candidal septicolysin‐like protein, potential reductase‐flavodoxin fragment, serine hydroxymethyltransferase, hypothetical proteins Cao19.10301(ATP7), CaO19.4716(GDH1), CaO19.11135(PGK1), CaO19.9877(HNT1) by P. aeruginosa LPS. Our data imply that bacterial LPS inhibit C. albicans biofilm formation and hyphal development. The P. aeruginosa LPS likely target glycolysis‐associated mechanisms during candidal filamentation.